Economic and social issues in agricultural biotechnology - Evenson, Robert E. (Robert Eugene), 1934-; Santaniello, V.; Zilberman, David, 1947- (CABI, 2002)
This book presents 21 selected revised and edited papers from the 4th and 5th meetings of the International Consortium on Agricultural Biotechnology Research, held in Italy in 2000 and 2001. Topics covered include: intellectual property rights and technological exchange; public-private issues; genetic technologies and methods; developing country experiences; and international models. The book will be of interest to those working within agricultural biotechnology and agricultural economics. The book has a subject index.